Analisis Faktor-Faktor Kepatuhan Menjalani Hemodialisis Pada Pasien Penyakit Ginjal Kronik Di RS Roemani - Aprianti, Mila (Journal of Comprehensive Science, 2025)
Chronic kidney disease (CKD) is a progressive decline in kidney function that can end in kidney failure. Patients with CKD are treated with hemodialysis 1 or 2 times a week on an ongoing basis. Hemodialysis has a physical and psychological impact on patients. Compliance with hemodialysis therapy is an important thing that needs attention. Education level, knowledge, distance to a single place and economic status are factors for adherence to undergoing hemodialysis. The aim of this study was to describe and analyze the level of education, level of knowledge, distance to the hospital, economic status of patients with chronic kidney disease adherence undergoing hemodialysis at Roemani Hospital. Methods : Observational method with a Cross Sectional approach. The total population is 96, the sample is taken using the total sampling technique with regard to the inclusion and exclusion criteria. Data collection used a self-data questionnaire, knowledge and adherence to undergoing hemodialysis. The data obtained were analyzed by chi-square test. Results : Obtained 80 samples, in the chi-square correlation test for educational level with hemodialysis adherence p-value = 0.001. Knowledge level with hemodialysis compliance p-value = 0.001 and PR-value 5.88. Distance between residence and adherence to hemodialysis p-value = 0.001 and PR-value 1.25. Economic status with hemodialysis compliance p-value = 0.013. Conclusion : There is a relationship between education level, level of knowledge, distance to hospital and economic status with adherence of chronic kidney disease patients undergoing hemodialysis at Roemani Hospital.